PENGARUH PEMBERIAN KUNYIT DAN TEMULAWAK MELALUI AIR MINUM TERHADAP GAMBARAN DARAH PADA BROILER - Fahrurozi, Nopendika; Tantalo, Syahrio; Santosa, Purnama Edy (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
This study aimed to determine the effect of tumeric and curcumin on the amount of erythrocytes,leucocytes, and haemoglobin level in the broilers. This study was conducted from Frebruary –March 2013, in the unit of trial poultry house of Rama Jaya Lampung, located in Fajar Baru IIVillage, Jati Agung District, South Lampung. 180 Broilers strain Cobb were used in this study.This study consisted of three treatments, P0: usual drinking water; P1: tumeric boiled water 10g/600 ml; and P2: curcumin boiled water 10 g/600 ml. Each treatment consisted of 6 replicationswith 10 broilers for each replication. 1 broiler was taken from each block of 18 cage blocks forbeing a sample. Then, data obtained were variance analyzed by using significant level of 5% . Ifsignificant result was obtained on the variance analysis, Least Significantly Different Test wascontinued on the significant level of 5% (Steel dan Torrie, 1993).The result of this study showed that tumeric and curcumin were not significantly different(P>0,05) on the amount of erythrocytes, leucocytes, and haemoglobin level. The average of theamount of erythrocytes were P0 (1.128.333/mm3), P1 (1.440.000/mm3), dan P2 (1.386.667/mm3).The average of the amount of leucocytes were P0 (7.767/mm3), P1 (7.792/mm3), dan P2(7.908/mm3). The average of haemoglobin level were P0 (7,6 g/100ml), P1 (8,5 g/100ml), dan P2(8,5 g/100ml). On the treatments given with tumeric and curcumin, they had higher average oferythrocytes, leucocytes, and haemoglobin level than the one without treatments.